Cross-Border Tax Avoidance: Foreign and Internal Determinants in Indonesian Multinationals - Martini Martini; Rismawandi Rismawandi (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
Although tax avoidance can be viewed as a corporate strategy to increase profits, it may negatively affect Indonesia’s image among international investors who place importance on tax compliance and integrity. This study offers recommendations on how to create a healthy and sustainable investment environment. The research aims to examine, evaluate, and measure the extent to which foreign ownership, the presence of foreign directors, transfer pricing practices, and a firm’s status as a multinational company influence tax avoidance behavior. The population consists of multinational companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024, with purposive sampling applied as the sampling technique. Data were analyzed using SPSS software. The findings show that foreign ownership has a positive and significant effect on tax avoidance, while foreign directors and transfer pricing practices do not exhibit a significant influence. Conversely, multinational company status has a negative and significant impact on tax avoidance.